2015
DOI: 10.4162/nrp.2015.9.2.150
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the DASH diet education program with omega-3 fatty acid supplementation on metabolic syndrome parameters in elderly women with abdominal obesity

Abstract: BACKGROUND/OBJECTIVESThe purpose of this study was to investigate the overall effects of a tailored Dietary Approaches to Stop Hypertension (DASH) nutritional intervention program which included omega-3 fatty acids supplementation, on dietary self-efficacy, dietary knowledge, and dietary behaviors in Korean elderly women with abdominal obesity. Furthermore, we investigated the effects of the program on metabolic syndrome parameters including the antioxidant capacities in these subjects.SUBJECTS/METHODSA random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 31 publications
1
16
1
1
Order By: Relevance
“…A study by Tangney et al (2016) found differences in DASH adherence by measurement method in Hispanics/Latinos, further suggesting that DASH scoring may need to be adapted to Hispanic/Latino cuisine and culture. These findings may explain why, despite prior reports of associations between DASH and diabetes/insulin resistance in Hispanics/Latinos (Corsino et al, 2012) and DASH and MetS in Middle Eastern (Aljefree and Ahmed, 2015; Azadbakht et al, 2005; Saneei et al, 2015), Asian (Choi and Choi-Kwon, 2015), Mediterranean (Pimenta et al, 2015), African-American (Rankins et al, 2007), and Western (Nazare et al, 2013; Root and Dawson, 2013) populations, we and others (Mattei et al, 2017) found largely null associations among Hispanics/Latinos.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…A study by Tangney et al (2016) found differences in DASH adherence by measurement method in Hispanics/Latinos, further suggesting that DASH scoring may need to be adapted to Hispanic/Latino cuisine and culture. These findings may explain why, despite prior reports of associations between DASH and diabetes/insulin resistance in Hispanics/Latinos (Corsino et al, 2012) and DASH and MetS in Middle Eastern (Aljefree and Ahmed, 2015; Azadbakht et al, 2005; Saneei et al, 2015), Asian (Choi and Choi-Kwon, 2015), Mediterranean (Pimenta et al, 2015), African-American (Rankins et al, 2007), and Western (Nazare et al, 2013; Root and Dawson, 2013) populations, we and others (Mattei et al, 2017) found largely null associations among Hispanics/Latinos.…”
Section: Discussioncontrasting
confidence: 65%
“…One such index is the Dietary Approaches to Stop Hypertension (DASH) diet, originally developed to control or prevent hypertension (Lin et al, 2007; Conlin et al, 2000). Numerous prior studies found associations between DASH diet and metabolic syndrome or one or more of its components (Aljefree and Ahmed, 2015; Azadbakht et al, 2005; Choi and Choi-Kwon, 2015; Nazare et al, 2013; Pimenta et al, 2015; Rankins et al, 2007; Root and Dawson, 2013; Saneei et al, 2015). However, few studies examined DASH diet among diverse Hispanics/Latinos in connection with metabolic syndrome or its components (beyond blood pressure) (Corsino et al, 2012; Harmon et al, 2015; Otto et al, 2015; Staffileno et al, 2013).…”
Section: Introductionmentioning
confidence: 98%
“…Another cross-sectional study using data from the National Health and Nutrition Survey, Japan found that better adherence to the DASH diet was inversely associated with metabolic risk factors including waist circumference, total cholesterol, LDL cholesterol, and BMI [ 52 ]. This observational evidence suggests a beneficial effect of the DASH diet for metabolic syndrome, and findings from intervention studies seem to agree [ 53 , 54 ]. Indeed, one randomized-controlled trial investigated the effect of an 8-week individualized DASH diet education intervention plus omega-3 fatty acid supplementation on metabolic syndrome parameters in elderly South Korean women [ 53 ].…”
Section: The Dash Diet and Cardiometabolic Health In East Asiamentioning
confidence: 87%
“…This was similar to the findings in preceding studies that reported behavioral skills played an important role in practicing healthy behavior for Mets [ 15 , 16 ]. Also, increased behavioral skills were related to improved healthy behaviors, such as balanced diet and increased physical activity [ 21 , 51 ]. Also, behavioral strategies, such as repeating the sentence “I will walk at least 30 min” induced long term practices of healthy behaviors [ 14 , 50 ].…”
Section: Discussionmentioning
confidence: 99%